A Linguistic Comparison of Appropinquation Verbs in English and Arabic: Structure, Meaning, and Usage (Journal of the College of Basic Education, 2026)
This study presents a contrastive analysis of appropinquation verbs in Arabic and English. Appropinquation verbs, a well-defined grammatical category in Arabic grammar (أفعال المقاربة), express concepts of temporal imminence, inception, and hopeful expectation. The research investigates the significant typological differences between the two languages: Arabic employs a closed set of synthetic verbs with specific syntactic constraints, requiring a subject in the nominative and a predicate in the accusative case (typically a present tense verb). Since English has no direct grammatical counterpart, it instead uses a variety of multi-word expressions to convey similar meanings, such as the modal phrase 'be about to,' the phrasal verb 'set about,' and catenative verbs like 'begin. The results show that Arabic and English convey proximity in distinct ways: Arabic uses morphological forms, while English uses phrasal structures.The research aims to expand the body of knowledge in the field of comparative linguistics and semantics, through theoretical analysis and comparison between two linguistic systems. The results of this theoretical research may lay the groundwork for subsequent applied research, such as developing materials for teaching Arabic or English to learners, improving machine translation tools. This study adopts a descriptive–contrastive approach to examine syntactic and semantic differences between Arabic and English appropinquation constructions.”